2020
DOI: 10.3390/ijerph17217855
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Cryotherapy Attenuates Oxi-Inflammatory Response Following Skeletal Muscle Injury

Abstract: The oxi-inflammatory response is part of the natural process mobilizing leukocytes and satellite cells that contribute to clearance and regeneration of damaged muscle tissue. In sports medicine, a number of post-injury recovery strategies, such as whole-body cryotherapy (WBC), are used to improve skeletal muscle regeneration often without scientific evidence of their benefits. The study was designed to assess the impact of WBC on circulating mediators of skeletal muscle regeneration. Twenty elite athletes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 49 publications
1
19
0
1
Order By: Relevance
“…Peroxide levels distinctly worse compared to another group of heavy workers [10] independent of adequate antioxidant sustenance. A reason for this might be the ambient temperature [20] and environmental conditions, such as smoke or metal residues that are harmful to health [1,4]. This is consistent with a recent publication that found increased oxidative stress in workers exposed to different types of nanomaterials compared to office workers [21,22].…”
Section: Discussionsupporting
confidence: 79%
“…Peroxide levels distinctly worse compared to another group of heavy workers [10] independent of adequate antioxidant sustenance. A reason for this might be the ambient temperature [20] and environmental conditions, such as smoke or metal residues that are harmful to health [1,4]. This is consistent with a recent publication that found increased oxidative stress in workers exposed to different types of nanomaterials compared to office workers [21,22].…”
Section: Discussionsupporting
confidence: 79%
“…Muscle injury repair includes three sequential and programmed processes: (1) the inflammatory response; (2) SC activation, proliferation, differentiation, and fusion; and (3) muscle fiber maturation and remodeling of new muscle fibers [35][36][37]. Pathological analysis showed that Ltf knockout delayed the repair of damaged skeletal muscle, manifested as a smaller area of new muscle fibers and more collagen fiber formation compared to WT control mice.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a group of volleyball players who underwent a 2-week training program, daily WBC led to an improvement in the growth factor profile [brainderived neurotrophic factor (BDNF) and insulin-like growth factor 1 (IGF-1)] that may sustain muscle regeneration and limit the deterioration of physical performances (Jaworska et al, 2018). However, in elite athletes subjected to randomized WBC (3 min, −120 • C, two times a day for 7 days) or no treatment, despite the significant reduction of reactive oxygen and nitrogen species (H 2 O 2 and NO) and the concentrations of the pro-inflammatory mediators IL-1β and CRP, cryostimulation caused the decrease in IGF-1, BDNF, hepatocyte growth factor (HGF), platelet-derived growth factor (PDGFBB), and vascular endothelial growth factor (VEGF; Zembron-Lacny et al, 2020). These findings further suggest that WBC may act as an exercise-mimetic treatment, possibly associated to the coldinduced muscle contraction, stimulating the expression of those myokines whose release are typical following an acute bout of physical activity.…”
Section: Wbc-pbc Can Diminish Inflammation and Induce Analgesic Effectsmentioning
confidence: 99%